PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 -2014 - Irmawati, 12.05.51.0004; Sudiyatno, Bambang (Students Journal of Economic and Management, 2016)
This study aims to determine the effect of asset structure, profitability, sales growth and liquidity to capital structure listed on the Indonesia Stock Exchange Period 2012-2014. This study used a sample of manufacturing companies listed in Indonesia Stock Exchange. Based on the observations, the number of companies listed on the Indonesia Stock Exchange during the study period between the years 2012-2014 was 84 companies for 3 years as many as 252 data. Methods of data analysis using linear regression. The test results showed that the structure of assets did not significantly influence the capital structure at manufacturing companies in BEI, profitability and liquidity significantly and negatively related to capital structure in manufacturing companies in BEI, and sales growth positive effect was not significant to the capital structure in manufacturing companies in BEI. Keywords: asset structure, profitability, sales growth, liquidity and capital structure. Â